Incidence of Early Peripheral Venous Catheter Replacement in Surgical Patients - Promdongdee, Nipapron; Siriphanyakhun, Poonsikorn; Sirivanasandha, Busara (Journal of Health Science of Thailand, 2017)
Early peripheral venous catheter replacement than suggested in the guideline may cause worst effect on both patients and the hospital in term of increased unnecessary workload and cost. This study aims to determine the incidence and risk factors of this problem. Prospective cohort study was performed in 200 patients from the surgical and orthopedic wards in Siriraj hospital. Early peripheral venous catheter replacement before 72 hours was observed in 58 patients with the incidence of 29%. Risk factors were found to be (1) patients with cardiovascular diseases (p=0.010, OR 4.5), (2) type of working unit of the first canulation (p=0.023, OR 4.5), (3) canulation site (p = 0.00, OR 12.6), (4) outside ward transference (p < 0.001, OR 35.9), (5) methods of intravenous therapy (p = 0.001, OR 4.2), and (6) type of intravenous substances (p<0.001, OR 13.7). These study results are useful for raising standard of care and the improvement of guideline for caring patients with peripheral venous catheter in Siriraj hospital and elsewhere.